Maternal caesarean section infection (MACSI) in Sierra Leone: a case–control study. (27th February 2020) - Di Gennaro, F.; Marotta, C.; Pisani, L.; Veronese, N.; Pisani, V.; Lippolis, V.; Pellizer, G.; Pizzol, D.; Tognon, F.; Bavaro, D. F.; Oliva, F.; Ponte, S.; et al.
Abstract: Sierra Leone is the country with highest maternal mortality and infections are the underlying cause in 11% of maternal deaths, but the real burden remains unknown. This study aims to determine the incidence and risk factors of surgical site infection (SSI) post-caesarean section (CS) in women admitted to Princess Christian Maternity Hospital (PCMH) in Freetown, Sierra Leone. A prospective case–control (1:3 ratio) study was implemented from 1 May 2018 to 30 April 2019 and 11 women presenting with suspected or confirmed infection post-CS were screened for inclusion as a case. For each case, three patients undergoing CS on the same day and admitted to the same ward, but not presenting with SSI, were selected as controls. The post-CS infection rate was 10.9%. Two hundred and fifty-four clinically confirmed cases were enrolled and matched with 762 control patients. By multivariable analysis, the risk factors for SSI were: being single (odds ratio (OR) 1.48, 95% confidence interval (CI) 1.36–1.66), low education level (OR 1.68, 95% CI 1.55–1.84), previous CS (OR 1.27, 95% CI 1.10–1.52), presenting with premature membranes rupture (OR 1.49, 95% CI 1.18–1.88), a long decision–incision time (OR 2.08, 95% CI 1.74–2.24) and a high missing post-CS antibiotic doses rate (OR 2.52, 95% CI 2.10–2.85).